IMPLEMENTASI PELATIHAN AROMATERAPI ROLL-ON DAN SERUM HERBAL BERSAMA STIKES ISFI BANJARMASIN, PT NATURINDO FRESH, DAN CV NATURONAL CREATAMA INDONESIA - Kintoko; Hardi Astuti Witasari; Yusron Umar; Erna Prihandiwati; Yugo Susanto (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Aromatherapy training is an empowerment strategy designed to introduce safe and rational use of essential oils. This activity was conducted through collaboration between STIKES ISFI Banjarmasin as the academic partner, PT Naturindo Fresh as the training venue and herbal garden facility, and CV Naturonal Creatama Indonesia as the implementing entity. The training aimed to increase participants’ knowledge and skills on aromatherapy foundations, essential oil safety, blending techniques, and product formulation in the form of roll-on and herbal serum. Using a one-group pretest–posttest design, participants joined theoretical sessions, herbal garden tours, factory production observations, and practical formulation activities. The results showed a significant increase in knowledge, ranging from 92–96% across all evaluated components. The program effectively enhanced practical formulation skills and provided potential opportunities for small-scale entrepreneurship in aromatherapy-based products.